Ileal and colonic fatty acid profiles in patients with active Crohn's disease. Issue 10 (October 1994) - Bühner, S; Nagel, E; Körber, J; Vogelsang, H; Linn, T; Pichlmayr, R
Abstract : In patients with active Crohn's disease and in a control group the fatty acid profiles in the whole lipid fraction of ileal and colonic mucosal biopsy specimens were determined by capillary gas chromatography. The biopsy specimens in Crohn's disease patients were taken from the inflamed terminal ileum as well as from the inflamed and macroscopically normal colon. Compared with controls the fatty acid distribution in the inflamed ileal mucosa was significantly characterised by (a) a decrease of 18:2 n6 and 18:3 n3 accompanied by a substantial increase of the highly polyunsaturated fatty acids 20:4 n6, 22:4 n6, and 22:6 n3 and (b) a higher unsaturation index of total fatty acids compared with controls. These changes were similar in the inflamed colon. Additionally, both the inflamed and the macroscopically normal colonic mucosa showed an increase of saturated (18:0) and a decrease of monounsaturated fatty acids (18:1 n9). Fatty acid profiles of ileum and colon showed side variations in controls, but not in the Crohn's disease group. These data suggest that in Crohn's disease changes in the distribution of polyunsaturated fatty acids seem to be the general feature of inflamed mucosa in small and large intestine. Results further suggest that colonic fatty acid metabolism in Crohn's disease is altered by degrees, showing changes in saturated and monounsaturated fatty acids as an additional, primary event.